The role of professional elites in shaping management practice: How the old mentalities condition the adoption of new management ideas - Seeck Hannele; Kantola Anu (Sage, 2025)
This study explores how the adoption of management ideas is conditioned by wider macro-level mentalities that are not company based but that instead reflect professionally or nationally rooted ways of managing. Drawing from studies on professional mentalities and practices, we study Finnish top executives working in globally operating multinational corporations in the metal and forestry industries, showing how, starting in the 1980s, they adopted new management practices during the rise of globalisation, market liberalisation and post-Fordism. Altogether, a traditional engineering mentality strongly conditioned the dissemination of new management ideas, which needed to adapt with the existing mentality. As a result, we find three ways of management idea dissemination: (a) new ideas had to fit in with the old business elite mentality, (b) new ideas were side-lined and belittled by the old mentality and (c) new ideas were smuggled into management by reframing and widening the old mentality. By extending Guillen's work on elite mentalities, the study contributes to the research on management ideas by exploring the role of societal macro-level mentalities in management learning, highlighting their role in times of societal transformation.